Cardiac structural and functional changes in old elderly patients with obstructive sleep apnoea–hypopnoea syndrome. (April 2014) - Sun, Yi; Yuan, Hai; Zhao, Miao-Qing; Wang, Yan; Xia, Ming; Li, Yan-Zhong
Objective: To investigate cardiac structural changes in elderly patients with obstructive sleep apnoea–hypopnoea syndrome (OSAHS) and the impact on left ventricular systolic and diastolic function. Methods: The study enrolled elderly patients with OSAHS and age-matched healthy control subjects. Cardiac structure, left ventricular diastolic function and left ventricular systolic function were measured using a Doppler ultrasound scanner and compared between the two groups. Results: The study included 136 patients with OSAHS and 50 healthy control subjects. There were significant differences in the echocardiography indicators that reflect cardiac structure, including interventricular septum, left ventricle posterior wall thickness, and left ventricular mass and mass index between the two groups. There were significant differences between the two groups in the ventricular septal early diastolic myocardial peak velocity/late diastolic myocardial peak velocity (Em/Am), mitral annulus Em/Am, and left ventricle posterior wall Em/Am. There were also significant differences in the indicators of interventricular septum, mitral annulus and left ventricular posterior wall systolic peak velocity between the two groups. Conclusion: Elderly patients with OSAHS demonstrated cardiac structural changes and their left ventricular diastolic and systolic functions were significantly diminished.